Elucidating the genomic and transcriptomic profiles contributing to the overall survival of acute myeloid leukaemia patients with normal karyotype in Malaysia - Ambayya @ Ampiah, A Angeli (Universiti Sains Malaysia, 2024)
Acute myeloid leukaemia-normal karyotype (AML-NK) comprises almost half of the AML subtypes and exhibits heterogeneity in overall survival (OS). Hitherto, the genomic and transcriptomic profiles of AML-NK that contribute to OS remain veiled. Therefore, this study aimed to elucidate the genomic and transcriptomic profiles of AML—NK patients predisposed to their overall survival. Deep transcriptome sequencing using NovaSeq 6000 (200M reads per sample, paired-end) was performed on 51 AML-NK patients at diagnosis (DX), 14 paired first remission (CR1) samples and 12 healthy controls. Targeted DNA sequencing (Archer HGC VariantPlex Myeloid panel) was performed using NovaSeq 6000 on eight paired DX and CR1 with sequencing depths of 3M and 30M, paired-end, respectively. The transcriptome sequencing yielded discoveries of differentially expressed genes (DEGs) profiles and functionally enriched pathways in several subgroup analyses as follows: AML-NK patients with the healthy normal groups (5126 DEGs), paired DX and CR1 (5621 DEGs), FLT3/NPM1 genotypes (750 DEGs), and OS of below and above five years (211 DEGs). There were 27 types of fusion genes (n=68) discovered in this study, of which several novel recurrent fusion genes, including LATS2-SAP18 and HOXA3-HOXA9, exhibited prognostic relevance in patients with OS below five years. A total of 74,604 deleterious variants (88.3% single nucleotide variants (SNVs) and 11.7% insertion-deletions (InDels)) were identified in the 51 AML-NK patients. Five SNVs were candidates for targeted therapies, whereas prognostically significant frameshift InDels were detected in the NPM1, DNMT3A and FLT3 genes. The targeted DNA sequencing included eight AML-NK samples and revealed 208 findings (122 in the DX samples and 86 in the CR1 samples), leading to the identification of suitable biomarkers for minimal residual disease monitoring. The highlight of this study was a prognostic scoring model developed based on the findings of the OS below and above five-year comparison. Six significantly upregulated genes in the (FHL1, SOCS2, IL17RC, STAT4, INHBA and TNFSF8) in the JAK-STAT signalling pathway and cytokine-cytokine receptor interaction were included in the prognostic scoring model that revealed that the gene scores were an independent prognostic marker in the AML-NK patients in this cohort. Ultimately, the findings were depicted in an oncoprint that reflected how the genomic discoveries in this study improvised the patient’s risk stratification for outcome predictions and potential targeted therapies. Hence, this multifaceted study has provided new insights into the genomic and transcriptomic profiles of AML-NK patients and shed light on their heterogeneous clinical outcomes